The Role of Islamic Religion Teachers in Overcoming Egocentrism Among Students at Madrasah Ibtidaiyah Ibrahimy Sukorejo - Alfina Wildatul Fitriyah; Moh. Bahzar; Wingkolatin Wingkolatin; Siti Munawati; Indah Wahyu Ningsih; Yunita Abdullah Aji (Universitas Nurul Jadid, 2024)
Islamic religion teachers act as educators who not only teach religious materials, but also shape students' characters. This study aims to explore the role of Islamic religion teachers in overcoming students' egocentrism in madrasah. Egocentrism, which is characterized by excessive focus on oneself, can hinder students' social interaction and character development. The research method used is qualitative, with data collection techniques through in-depth interviews, observation, and documentation. The research subjects involved religion teachers, students, and parents at Madrasah Ibtidaiyah Ibrahimy Sukoerjo, Situbondo, East Java. The results showed that religion teachers have an important role in instilling moral and ethical values through interactive teaching methods. The strategies applied include example-based learning, group discussions, and social activities that prioritize empathy and cooperation. In addition, parental support and a positive school culture contribute significantly to reducing students' egocentrism. However, challenges such as a lack of training for teachers and academic pressures remain limiting factors. The findings emphasize the importance of collaboration between teachers, parents and the community in creating a learning environment that supports students' character development. This research is expected to provide insights for the development of more effective educational programs in shaping empathic and social attitudes among madrasah students.